Investigation of Teacher Candidates' Nature of Science Beliefs In Terms of Gender, Program, and Class Level - Ali Çetin; Mustafa Kahyaoğlu (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
This research aims to examine teacher candidates' nature of science beliefs in terms of certain variables (gender, program, and class level). The participants of the research are 364 teacher candidates studying at the faculty of education of a public university in three programs; science education, elementary mathematics education, computer education, and instructional technology. Convenience sampling was applied and a relational screening model from descriptive research design was used.